Karakteristik Fisikokimia Fruit Leather Jambu Biji (Psidium guajava L.) dengan Variasi Konsentrasi Gum Aran dan Sukrosa - Zaidiyah Zaidiyah; Cantika Putri Malini; Yusya Abubakar (Jurnal Teknologi dan Industri Pertanian Indonesia, 2021)
Guava is perishable fruit and has  relatively short shelf life, so that many of these fruits are damaged and eventually discarded. Guava can be processed into fruit leather, a thin and elastic sheet properties, which is an alternative processing method to extend shelf life of guava. Nevertheless, the pectin content in guava was apparently not enough to desired plasticity properties in fruit leather, therefore it is necessary to add arabic gum to improve the texture and sucrose to improve the taste. This study aims to determine the effect of the addition of sucrose and gum arabic on the physicochemical characteristics and consumer acceptance of fruit leather. This study was conducted using a factorial Completely Randomized Design with two factors, concentration of gum arabic stabilizer with 3 levels (0,3%, 0,6% and 0,9%) and the concentration of sucrose with 3 levels (5%, 10% and 15%). The average value of each parameter were pH 4.93; total dissolved solids 68.27; ascorbic acid 97.04 mg/100 gr; water content 10.38%; total acid 0.39%; ash content 1.19%; antioxidant activity 49.67%, and organoleptic value of colour, aroma, taste and texture were 2.78 (neutral), 2.64 (neutral), 2.44 (dislike) and 2.75 (neutral). Based on the ranking test, the best guava fruit leather with the addition of 0.9% gum arabic and 15% of sucrose.